A review of psychosocial learning environment - Jamaluddin, Nor Sa’adah; Abd. Kadir, Suhaida; Alias, Siti Noormi; Abdullah, Arnida (Human Resource Management Academic Research Society, 2021)
The education field is one of the aspects that have been linked to the economic field. Based on the Malaysian Education Blueprint 2013–2025, the learning environment is one of the aspects that should be improved in order to achieve the best academic performance. The aim of this study is to review a learning environment that influences achievement in the education field. This paper explores the meaning of the psychosocial learning environment by various researchers and even explores one of the most popular dimensions of the psychosocial learning environment, such as teacher and student relationships that is believed to be capable of affecting the academic performance. A good relationship between the teacher and student can leave positive impacts on the student’s level of motivation and attitude towards their learning. The findings of previous researchers were also included to support the arguments used in this study.